Wajah Baru Pesantren di Madura; Studi tentang Pemikiran, Dinamika dan Kontribusi Pondok Pesantren Mambaul Ulum Pamekasan - Hidayatul Mutmainah; Sitti Atiyatul Mahfudoh (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2021)
In general, pesantren prioritize Islamic religious knowledge over general subjects. This can be seen from the learning process that uses classical Islamic books, traditions and some of their activities. This study aims to analyze the new scheme of pesantren in Madura where the people are known to be thick with religious knowledge. This research is descriptive qualitative with the object of research is pesantren Mambaul Ulum Bata-Bata Pamekasan Madura. From this research, the writer sees that pesantren Mambaul Ulum – which is one of the big pesantren in Madura – is now showing its new face. The pesantren is now more dynamic, open, and capable of being the driver of the desired change. Although the pattern of change is sporadic, pesantren Mambaul Ulum Bata-bata has taken an agreement to maintain the pesantren tradition that has been built for a long time and follows the trends of the times and technology. The form of change emphasizes aspects of the education system, curriculum, learning patterns and so on. By implementing an integrated model of salaf and khalaf education, this pesantren is able to influence the surrounding community in developing Islamic education.